Emerging Digital Health Technologies In Diabetes Care: Clinical Outcomes, Patient Experience, And Evolving Roles Of Nurses, Dentists, Laboratory, Health Informatics, And Radiology Professionals – A Systematic Review (The Review of Diabetic Studies, 2025)
Background:Emerging digital health technologies are increasingly transforming diabetes care by enhancing clinical outcomes, patient experience, and care coordination. The integration of telehealth, mobile health (mHealth), remote monitoring, and artificial intelligence (AI) has reshaped clinical workflows and expanded the roles of multidisciplinary healthcare professionals. This systematic review aimed to synthesize current evidence on digital health interventions in diabetes care and to examine the evolving responsibilities of nurses, dentists, laboratory professionals, health informatics specialists, and radiology professionals.Methods:A comprehensive literature search was conducted across major electronic databases, identifying more than 1,050 records. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. After removal of duplicates and screening based on predefined inclusion and exclusion criteria, 20 studies were included for qualitative synthesis. Eligible studies evaluated digital health interventions in diabetes care, including telehealth platforms, mHealth applications, remote patient monitoring, and AI-assisted diagnostic and decision-support tools.Results:The included studies consistently reported improvements in glycemic control, patient engagement, self-management, and interprofessional collaboration. Nurses played a central role in patient education, virtual follow-up, and remote monitoring. Radiology professionals contributed through AI-enhanced imaging and early detection of diabetes-related complications. Dentists supported integrated care by incorporating oral health monitoring into digital systems, while laboratory and health informatics professionals facilitated data integration, clinical decision support, and continuity of care. Key implementation challenges included limited digital literacy, insufficient training, and infrastructure constraints.Conclusion:Digital health technologies are redefining diabetes care and strengthening multidisciplinary collaboration. Optimizing their impact requires continuous professional training, investment in digital infrastructure, and integrated care models. Future research should focus on scalable implementation strategies and long-term evaluation of clinical and patient-centered outcomes.